Factors affecting work stress in university - Fatwa Tentama; Surahma Asti Mulasari; Netty Merdiaty (International Journal of Public Health Science (IJPHS), 2019)
Workload and work motivation are factors that can affect work stress. This study aims to empirically examine the effect of workload and work motivation on work stress on employees at X University. The research participants were non-educational employees at X University, have permanent employee status, and had worked for at least 1 year. The sampling technique used was simple random sampling technique. Data collection was carried out using workload scale, work motivation scale and work stress scale. Data analysis using multiple linear regression techniques. The results showed that workload and work motivation simultaneously affect work stress. Similarly, workload and work motivation independently also has a very significant influence on work stress.